Testing distance characteristics and reference values for ice-hockey straight sprint speed and acceleration. A systematic review and meta-analyses. - Stastny, Petr; Musalek, Martin; Roczniok, Robert; Cleather, Daniel; Novak, Dominik; Vagner, Michal (Biology of Sport, 2023)
Ice-hockey requires high acceleration and speed sprint abilities, but it is unclear what the distance characteristic is for measuring these capabilities. Therefore, this systematic meta-analysis aims to summarize the sprint reference values for different sprint distances and suggest the appropriate use of ice-hockey straight sprint testing protocols. A total of 60 studies with a pooled sample of 2254 males and 398 females aged 11–37 years were included. However, the pooled data for women was not large enough to permit statistical analysis. The sprint distance used for measuring the reported acceleration and speed was between 4–48 m. Increased test distance was positively associated with increased speed (r = 0.70) and negatively with average acceleration (r = -0.87). Forward skating sprint speed increases with the measured distance up to 26 m and do not differ much from longer distance tests, while acceleration decreases with a drop below 3 m/s at distances 15 m and longer. The highest acceleration (5.89 m/s 2 peak, 3.31 m/s2 average) was achieved in the shortest distances up to 7 m which significantly differs from 8–14 m tests. The highest speed (8.1 m/s peak, 6.76 m/s average) has been recorded between 26–39 m; therefore, distances over 39 m are not necessary to achieve maximum speed. Considering match demands and most reported test distances, 6.1 m is the recommended distance for peak acceleration and 30 m for peak speed. The sprint time, acceleration, and speed of each individual and the number of skating strides should be reported in future studies.